2019
DOI: 10.31665/jfb.2019.6189
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer micro-dosing and harvesting time of indigenous leafy vegetables affect in vitro antioxidant activities

Abstract: Plant nutrient management can influence the type and level of polyphenolic compounds within leafy vegetables. Therefore, we investigated the effects of fertilizer micro-dosing and harvest time on antioxidant activities of aqueous polyphenolic extracts from Amaranthus cruentus, Ocimum gratissimum and Solanum macrocarpon. Plants were cultivated using urea alone or combined with cattle manure for three staggered harvest periods. Polyphenolics profile (RP-HPLC), DPPH, hydroxyl and superoxide radical scavenging act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…Foods are well known sources of enzyme inhibitory compounds, but their levels could be dependent on agronomic practices, which are critical for defining crop productivity, nutrient composition, and food availability. Therefore, in order to ensure food supply and increase crop productivity, the positive effect of mineral fertilizers cannot be overemphasized ( 28 , 29 ). The use of fertilizer micro-dosing gives promising results in terms of crop productivity and farmers' income when compared to the traditional fertilizer broadcasting method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foods are well known sources of enzyme inhibitory compounds, but their levels could be dependent on agronomic practices, which are critical for defining crop productivity, nutrient composition, and food availability. Therefore, in order to ensure food supply and increase crop productivity, the positive effect of mineral fertilizers cannot be overemphasized ( 28 , 29 ). The use of fertilizer micro-dosing gives promising results in terms of crop productivity and farmers' income when compared to the traditional fertilizer broadcasting method.…”
Section: Introductionmentioning
confidence: 99%
“…The use of fertilizer micro-dosing gives promising results in terms of crop productivity and farmers' income when compared to the traditional fertilizer broadcasting method. Fertilizer micro-dosing is a method of fertilizer application in small quantities at an optimal depth and distance around the target crop such as leafy vegetables ( 29 , 30 ) and maize ( 31 ) either during the time of planting or some weeks after planting. Water is a universal solvent with numerous advantages as a green extraction solvent because it is cheap, non-flammable, non-toxic, environmentally friendly, and prevent pollution when compared to organic solvents ( 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous extracts of A. cruentus leaves showed antioxidant activity against the superoxide radical in the range from 1.0% to 46.9% [ 35 ]. The antioxidant activity of ethanol leaf extracts against the superoxide radical was measured as 1.08 ± 0.09%.g −1 DM (variety ‘Zobor’) and 1.63 ± 0.14%.g −1 DM (variety ‘Pribina’) in our research.…”
Section: Discussionmentioning
confidence: 99%
“…Gallic acid had 65.4 ± 0.85% activity, which is comparable to the aqueous extract. It has also been found that with increasing concentration of extract, the antioxidant activity against the hydroxyl radical increases in aqueous leaf extracts of A. cruentus [ 35 ]; it ranged from −2.7% to 68.9%. The substances present in the amaranth leaves of both varieties, ‘Pribina’ and ‘Zobor’, were more effective against the hydroxyl radical than they were against the superoxide, though in the latter case, it was due to the long incubation time (40 min).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation